2008
DOI: 10.3132/pcrj.2008.00057
|View full text |Cite
|
Sign up to set email alerts
|

How frequently are physiological variables recorded in the emergency room in patients with obstructive pulmonary diseases and pneumonia?

Abstract: Aim: To assess how frequently measurements of relevant physiological variables are made in patients presenting acutely to hospital with obstructive pulmonary diseases (OPD) and pneumonia.Methods: Patients admitted to three hospitals in western Norway with OPD (asthma or chronic obstructive pulmonary disease (COPD)) and/or pneumonia over a 75-day period were included in the study. The assessing physicians in the emergency room (ER) were asked to measure and record physiological variables according to normal pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
1
1
Order By: Relevance
“…No significant gender differences were found. Our results were similar to other studies that showed equal CAP male to female ratios 24 , 25 and contrary to another primary care study where women were disproportionately diagnosed with pneumonia. 19 Significant differences were observed in our study in terms of alcohol and smoking, indicating a male predominance.…”
Section: Discussionsupporting
confidence: 89%
“…No significant gender differences were found. Our results were similar to other studies that showed equal CAP male to female ratios 24 , 25 and contrary to another primary care study where women were disproportionately diagnosed with pneumonia. 19 Significant differences were observed in our study in terms of alcohol and smoking, indicating a male predominance.…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows that the records at emergency hospital departments do not systematically reflect variables that are crucial to diagnostic management. However, it should be borne in mind that in our study sample, the percentage of patients given a test of arterial blood gases (89%) is higher than that reported in other studies [5,25,26], and similar to that obtained in the AudiPOC 2012 national prevalence study (90%) [13]. Haegstad et al .…”
Section: Discussionsupporting
confidence: 83%
“…However, it should be borne in mind that in our study sample, the percentage of patients given a test of arterial blood gases (89%) is higher than that reported in other studies [5,25,26], and similar to that obtained in the AudiPOC 2012 national prevalence study (90%) [13]. Haegstad et al found that the diagnostic procedures least commonly performed in the emergency room were cutaneous oxygen saturation and peak expiratory flow [26]. In a recent comprehensive study by Roberts et al (2013), which included 384 hospitals in 13 countries, it was found that the failure to obtain spirometry results and the inconsistent use of oxygen and non-invasive ventilation were areas in need of improvement for COPD patients [27].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation